Rodzina - Cushman, Karen (New York : Dell Yearling, 2005)
A twelve-year-old Polish American girl is boarded onto an orphan train in Chicago with fears about traveling to the West and a life of unpaid slavery.
"A Dell Yearling book."
Wilson's Children
Wilson's Junior High School
School Library Journal starred
5.9
5-8
Keywords: Polish Americans -- Juvenile fiction; Polish Americans -- Fiction; Orphans -- Fiction; Orphan trains -- Fiction; Survival -- Fiction; West (U.S.) -- History -- 19th century -- Fiction; Historical fiction; Polish Americans -- Fiction; Orphans -- Fiction; Orphan trains -- Fiction; Survival skills -- Fiction; Western stories; Historical fiction